IMPLEMENTASI PAK KONTEKS GEREJA DI GKII TANDANG, SEMARANG - Semion Nuh; I Putu Ayub Darmawan; Edi Sujoko (Pengarah: Jurnal Teologi Kristen, 2019)
Christian Religious Education is a biblical and Christ-centered teaching and learning process. Christian education plays a role in directing a person toward the understanding of and maturity in Christ. This research was conducted as the continuation of the research conducted by the previous researcher that is Susanto. Susanto’s research found that Christian religious education has been conducted in GKII Tandang, however the previous research has not explained how is the implementation. For that reason, it is considered important to describe Christian Religious Education implemented in the congregation of GKII Tandang. For that purpose, the researcher collects datas through interviews with pastors, church governing body members and church members, then observes the fellowship activities and collects datas from church documentation. Based on the results of the research, it has been found that the Christian Religious Education in GKII Tandang is held through Sunday worship preaching, catechisms, cell group fellowship, categorical fellowship, open-air fellowship, and prayer and fasting. Thus, the study concludes that Christian Religious Education is carried out in the congregation through fellowship and teaching.